Результати і перспективи дослідження технології виготовлення керамічного посуду Середньої Наддніпрянщини XVI—XVIII ст. - Чміль, Л.В. (Археологія і давня історія України, 2018)
У статті розглянуто результати дослідження
технології виготовлення керамічного посуду Середньої Наддніпрянщини XVI—XVIII ст. — сировина,
формування, техніки декорування, випал. Аналізуються різні методи досліджень та перспективні
напрямки подальшого вивчення пізньосередньовічного та ранньомодерного гончарства. The paper focuses on studying ceramic ware production
technology in the 16th—18th centuries. The main
perspective methods for each production stage, such as
chemical, petrographic and trajectory have been considered,
as well as archaeological, sphragistic and ethnographic
sources have been analysed. The ware was made of kaolin clay with the addition
of sand. Glaze consisted of lead, sand and metallic oxide for color. Clay with the addition of metallic oxide, such
as iron, copper etc. was colorant for painting. The ware was formed with foot potter fast wheel by drawing from
a piece of clay. Decor represented relief or painting without or with glaze. The glaze was colored or colorless. The
ware was roasted in bicameral kilns with vertical movement of hot gases in oxidizing or reductive medium.
Perspective directions of the further study of pottery production technology can be physical and chemical
methods, petrography and experiment to verify results of the research.